CRITIQUE OF FUNCTIONALISM IN THE WORKS OF ANTHONY GIDDENS AND NORBERT ELIAS: A COMPARISON - Šņitņikovs, Aleksejs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The purpose of the paper is to assess the arguments of the critique of functionalism by Anthony Giddens and Norbert Elias. After being subject to severe criticism, terminology of functionalism is still a part of the lexicon of social scientists nowadays. Functionalist reasoning and concepts of functionalism are used in sociology, political science and economics, even though often without full awareness of its theoretical implications. Recent revival of interest in the works by Elias is connected with the search for a new theoretical and methodological foundation of sociology but his views on functionalism have remained largely unexplored. For the analysis presented in this paper, main theoretical works by Giddens and major works by Elias have been used. Positions of the authors have been analysed with respect to main concepts and principles of functionalism, such as function, needs, internalization of values, consensus, equilibrium, and the notions of power and individual. The study shows that while Giddens strived to reject functionalism and the concept of social function altogether, in the figurational approach developed by Elias it is possible to use some of the concepts of functionalism without necessarily accepting its controversial tenets.